Nature of child sexual abuse and psychopathology in adult survivors: results from a clinical sample in Scotland. Issue 6 (4th December 2013) - Bak‐Klimek, A.; Karatzias, T.; Elliott, L.; Campbell, J.; Pugh, R.; Laybourn, P.
Abstract : Accessible summary: Child sexual abuse (CSA) is highly prevalent. CSA survivors are likely to develop a range of mental health problems in adult life which vary widely in severity, duration, and form. While some survivors suffer a wide range of severe psychological problems others experience few, if any at all. There is no clear explanation for such differences in frequency and intensity of problems across survivors. The nature of abuse is considered to have a primary role in the development of mental health problems in adult life, although results of existing studies remain inconclusive. To our knowledge, this is the first study which investigates the relationship between a wide range of sexual abuse characteristics and the severity of psychopathological disorders in a large sample of adult CSA survivors who attended a specialist Psychotherapy Service for CSA survivors. CSA survivors in our study experienced severe sexual assault(s) in their early years and presented with severe pathology which could suggest a strong causal link. However, no significant association between the sexual abuse characteristics and psychopathology severity was detected. This may suggest that for severely disordered, treatment‐seeking CSA survivors other factors might have contributed to the development of the post‐abuse psychopathology. The present study adds to the growing body of evidence suggesting that CSA effects may be dependent on factors not necessarily related to the nature of the sexual abuse such as poor family relationships. The current study will contribute to clinicians' knowledge of the determinants of psychopathology among severely disordered, help‐seeking CSA survivors. Abstract: The relationship between history of childhood sexual abuse and psychopathology in adult life is well established. However, understanding of the mechanisms by which abuse exerts its effects is limited. To our knowledge, this is the first study which investigates the relationship between a wide range of sexual abuse characteristics (i.e. age at onset, frequency of assaults, number of perpetrators and their relationship to the victim) and the severity of psychopathological disorders in a large sample of adult child sexual abuse (CSA) survivors who attended a specialist Psychotherapy Service for CSA survivors. CSA survivors in our study experienced severe sexual assault(s) in their early years and presented with severe pathology which could suggest a strong causal link. However, none of the examined trauma characteristics significantly predicted severity of psychopathology. This may suggest that for severely disordered, treatment‐seeking CSA survivors post‐abuse psychopathology could be caused by other factors. The study adds to the growing body of evidence suggesting that CSA effects may be dependent on factors which are not necessarily related to the nature of sexual abuse. The study findings will help improve clinicians' insight into the determinants of psychopathology.